An Implementation of Selected Image Processing for Single and Multiple Processors: image processing (International Journal of Engineering and Computer Science, 2019)
Image processing contributes on many of the technological advancements today. It is widely used by the developing institutes as well as a source of important data. One of the main things that are considered through this process would be the length of time on dealing with the application of different routines, on these images. Thus, time, being a valuable criterion for the efficiency of the systems, demands a better way for how these images will be managed. With the given situation, the idea of integrating a number of computers to perform image manipulation is considered. This uses the idea of parallel computing.